(untitled) - Husa, Jaakko (Oxford, 2015)
This thought provoking introduction to the study of comparative law provides an in-depth analysis of all major comparative methodologies and theories and serving as a common sense guide to the study of foreign legal systems. It is written in a lively and accessible style and will prove to be indispensable reading to students of the subject. It also contains much that will be of interest to comparative law scholars, offering novel insights into commonplace methodological and theoretical questions and making a significant contribution to the field
Keywords: Comparative law,Luật so sánh